Literature review: nutrition supplementation for muscle fatigue in athletes - Mardiana, Mardiana; Kartini, Apoina; Sutiningsih, Dwi; Suroto, Suroto; Muhtar, Muhammad Solihuddin (Universitas Negeri Yogyakarta, 2023)
The use of natural or conventional-based supplementation has become a popular strategy among athletes seeking to reduce oxidative stress, improve recovery, and enhance athletic performance. This literature review searched four reputable international electronic databases, including PubMed, MedRxiv, Cochrane, and Clinical Trial.gov until December 2021, using Boolean operators with keywords and Mesh methods. The keywords used were